Análise das demonstrações contábeis : um estudo do desempenho econômico-financeiro da Cotraibi cooperativa dos transportadores de Ibiraiaras no período de 2019 - 2021 - Vivan, Felipe (2022)
Accounting is one of the main instruments available to managers and society in general for the control, management and inspection of business plans and actions. A presentation of excellence in companies represents an effective and highly necessary strategy to guarantee a correct framework, that is, the least onerous for the organization, with a maximization of profits and growth. The study aims to carry out the economic-financial analysis of the Cooperativa dos Transportedores de Ibiraiaras, which operates in the field of national and international transport from 2019 to 2021. After choosing the company, the calculations for the horizontal and vertical analysis were carried out, indicator analysis. For the conclusion, after the horizontal and vertical analysis calculations were made, graphs and tables were generated for a better understanding of them. With this, it was possible to observe that, in general, the company is in good financial health. The only caveat is for the Financial Cycle index, as it will be necessary for the cooperative to make new decisions for its improvement.